EFEKTIFITAS RENDAM KAKI AIR HANGAT SERAI DAN RENDAM KAKI AIR HANGAT JAHE MERAH TERHADAP PENURUNAN TEKANAN DARAHPADA LANSIA HIPERTENSI - Vina febrianti; Nur Hamim; Alwin widiyanto (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Hypertension is a chronic disease characterized by elevated blood pressure and can lead to serious complications if not properly managed. In the elderly, hypertension becomes a major concern due to decreased elasticity of blood vessels with aging. One simple non-pharmacological method that can be applied is warm foot soaking using natural ingredients such as lemongrass and red ginger. This study aimed to analyze the effectiveness of warm foot soak with lemongrass and red ginger in reducing blood pressure among elderly patients with hypertension. This research employed a quasi-experimental design with a two-group pre-test post-test approach. The sample consisted of 46 elderly individuals with hypertension, divided into two purposive groups, each comprising 23 respondents. The first group received warm foot soak with lemongrass, and the second group with red ginger, conducted for three consecutive days. Blood pressure was measured before and after the intervention and analyzed using paired t-test and independent t-test. The results showed that before the lemongrass foot soak, the average systolic and diastolic blood pressure was 153.70 mmHg and 93.04 mmHg,. Meanwhile, before the red ginger foot soak, the average systolic was 152.70 mmHg and diastolic 92.61 mmHg, with a reduction of 6.13 mmHg and 4.91 mmHg. Independent t-test results showed a significant difference between the two groups (p < 0.001), indicating that warm foot soak with red ginger is more effective than lemongrass in lowering blood pressure. This study is expected to serve as a reference for implementing simple, safe, and affordable non-pharmacological therapy for managing hypertension in the elderly, particularly in community settings. hypertension, elderly, foot soak, lemongrass, red ginger.